Nanowire sensors monitor bacterial growth kinetics and response to antibiotics - Ibarlucea, Bergoi; Rim, T.; Baek, C. K.; De Visser, J. A. G. M.; Baraban, Larysa; Cuniberti, Gianaurelio (Giovanni) (Lab on A Chip, 2017)
Miniaturized and cost-efficient methods aiming at high throughput analysis of microbes are of great importance for the surveillance and control of infectious diseases and the related issue of antimicrobial resistance. Here we demonstrate a miniature nanosensor based on a honeycomb-patterned silicon nanowire field effect transistor (FET) capable of detection of bacterial growth and antibiotic response in microbiologically relevant nutrient media. We determine the growth kinetics and metabolic state of Escherichia coli cells in undiluted media via the quantification of changes in the source-drain current caused by varying pH values. Furthermore, by measuring the time dependent profile of pH change for bacterial cultures treated with antibiotics, we demonstrate for the first time the possibility of electrically distinguishing between bacteriostatic and bactericidal drug effects. We believe that the use of such nanoscopic FET devices enables addressing parameters that are not easily accessible by conventional optical methods in a label-free format, i.e. monitoring of microbial metabolic activity or stress response.
CRIS-Team Scopus Importer:2022-04-14